Experimental and Numerical Studies on Steel-Encased Overlapping Column Transfer Assemblies - Feng Lin; Wenbin Sun (Journal of Asian Architecture and Building Engineering, 2017)
Force transfer in misaligned columns in building structures can be implemented using overlapping column transfer assemblies. Two 1/6 scaled models of overlapping column transfer assemblies were tested to investigate their mechanical behavior under monotonic loadings. Both specimens were constructed using reinforced concrete and had an overlapping ratio of 0.56, one of which was encased with a steel truss with a cross-sectional steel plate ratio of 3.73%. A finite element method-based model was built, verified and used for parametric studies. Results indicated that the load bearing capacities of the steel-encased assembly increased by 35% compared to that of the assembly without steel. The increase in cross-sectional steel plate ratios and decrease in overlapping ratios improved the load bearing capacities of steel-encased assemblies.